Evidence on Mortality in Liver Transplantation Candidates: Integrative Literature Review - Emanuelly Marinho Moreno, Stephani; Maia Marque, Daniella; Piccoli Prochnon, Nathalia; Maria Galvão, Cristina; Dal Sasso Mendes, Karina (Brazilian Journal of Transplantation, 2022)
The objective of this paper was to analyze the evidence available in the literature about mortality and its risk factors in liver transplantation candidates. An integrative literature review was carried out, based on the following steps: elaboration of the research question, search in the literature of primary studies, data extraction, studies evaluation, analysis and synthesis of the results, and review presentation. The Latin American and Caribbean Health Sciences Literature (LILACS), National Library of Medicine and the National Institutes of Health (PubMed), and Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases were accessed for the search. Primary studies that portrayed the liver transplantation candidates’ mortality, published in English, Portuguese, and Spanish, over the last five years were included. Among the eight studies analyzed, it was observed that the risk factors associated with mortality and identified in more than one study were: encephalopathy (n=3; 37.5%), model for end-stage liver disease (MELD) (n=3; 37.5%), frailty (n=3; 37.5%), body mass index (n=2; 25%), hepatocellular carcinoma (n=2; 25%), sex (women) (n=2; 25%), and ascites (n=2; 25%). It is expected that the synthesis of evidence supports the planning of the intervention aimed at prioritizing care for patients at higher risk of death, contributing to the quality of health care in liver transplantation.